2019
DOI: 10.1007/s12325-019-01000-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Online Prescription Management Systems on Biologic Treatment Initiation

Abstract: IntroductionPharmaceutical firms have begun offering online prescription management systems to facilitate prescription processing. This study evaluated the impact of the HUMIRA Complete Pro (HCPro) online prescription management system on the rate of abandonment and the time to first fill for patients prescribed adalimumab (ADA). A retrospective cohort analysis of patients initiating ADA treatment with or without use of the HCPro online prescription processing system was used to evaluate the impact of HCPro on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Comprehensive PSPs can help patients navigate insurance coverage requirements and assist with appealing denied coverage. Prior research has shown that participation in a PSP reduces both the abandonment rate and the time to initiation of ADA for patients with RA [27,31]. The PSP studied here has previously been shown in TIM-naı ¨ve populations to improve access to care, reduce abandonment, and increase adherence and persistence; the last of which in particular is associated with a reduced risk of hospitalizations [27,31,34,48].…”
Section: Multiple Moas Within Consistent Psp Services As High-value Carementioning
confidence: 73%
See 1 more Smart Citation
“…Comprehensive PSPs can help patients navigate insurance coverage requirements and assist with appealing denied coverage. Prior research has shown that participation in a PSP reduces both the abandonment rate and the time to initiation of ADA for patients with RA [27,31]. The PSP studied here has previously been shown in TIM-naı ¨ve populations to improve access to care, reduce abandonment, and increase adherence and persistence; the last of which in particular is associated with a reduced risk of hospitalizations [27,31,34,48].…”
Section: Multiple Moas Within Consistent Psp Services As High-value Carementioning
confidence: 73%
“…When a patient and provider make the shared decision that a change in treatment is appropriate, the transition can be complicated for patients, including navigating access to coverage, understanding financial implications, and logistics of initiating the new therapy, which can lead to treatment disruptions [26][27][28][29][30]. Evidence suggests utilization of support services can help patients initiate a new TIM faster and more successfully [27,31]. AbbVie (North Chicago, IL, USA) offers both a TNFi [adalimumab (ADA)] and JAKi [upadacitinib (UPA)] in the treatment of RA, and provides support services across products, including benefit verification resources, education materials on both treatment and financial assistance options, and nurse ambassadors to provide individualized support in achieving treatment goals [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] Though PSP use has been consistently associated with improved outcomes for patients initiating treatment, there is a paucity of evidence on (a) whether medication-taking behavior benefits are sustained throughout treatment due to the novelty of multifaceted PSPs and (b) the relationship between PSP participation and hospital visits due to rarity. [1][2][3][12][13][14] As immune-mediated diseases continue to rapidly increase in prevalence and economic burden, understanding the potential sustained value of PSP participation in helping patients adhere to their long-term treatment plan and avoid hospital visits should be of great interest to patients, providers, and payers. [15][16][17] Nonadherence to treatments for chronic therapies has long been recognized as a major contributor to excess hospitalizations and wasteful health care spending.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Prior studies demonstrated the impact of this PSP in improving access to treatment, medication-taking behavior, and costs, but studies were limited to the first 12 months of adalimumab treatment and did not examine hospital visits. 1,2,13,14 Sufficient data are now available to provide more complete evidence on the benefits of PSPs throughout the duration of treatment by examining the impact of PSP use on sustained medication-taking behavior and risk of hospital visits.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Other functionalities of patient portals such as e-messaging or secure messaging and patient education can improve patients’ involvement in their care [ 15 ] and their knowledge about their disease [ 19 ], respectively. Patients’ ability to refill medication through the portal allows them to efficiently refill medication, reducing the time they spend without medication, and as a consequence may improve their adherence and compliance with medication regime [ 17 , 20 ].…”
Section: Introductionmentioning
confidence: 99%